An evaluation of the performance of pile-driving formulas - Aleria, Felner C. (2002)
This study presents an evaluation of the performance of six (6) dynamic pile-driving formulas in the prediction of the ultimate pile capacities of forty-eight (48) prestressed, precast concrete piles driven into silty sands. The six pile-driving formulas studied are the Engineering News, Modified Engineering News, Hiley, Janbu, Schenk and Danish formulas Predicted capacities (Ru) are compared with measured capacities that were obtained using high-strain dynamic pile load tests and CAPWAP analysis (Rm), and correlated statistically using high-strain dynamic pile load tests and CAPWAP analysis (Rm), and correlated statistically using linear regression analysis. In addition, the tendency of the pile driving formulas to underestimate/overestimate the measured capacity was investigated based on log-normal distribution plots and values of the mean, standard deviation and coefficient of variation of the calculated (Ru/Rm) ratios. Finally ,the resutls of the statistical analyses were used to determine appropriate factors of safety for use with each pile-driving formula for the calculation of allowable pile capacities.
Results of the study show that the performance of the Hiley formula was relatively superior, followed closely by the Janbu, Schenk and Danish formulas. Calculated safety factors for the Hiley, Janbum Schenk and Danish formulas ranged from 2.0 to 4.40. On the other hand, capacity predictions obtained using the Engineering News and Modified Engineering News formulas were found to have very poor correlations with and tend to significantly overpredict measured capacities, resulting to very high calculated safety factors greater than 8.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Piling (Civil engineering)